![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Do \(a^x=bc;b^y=ca;c^z=ab\Rightarrow a^x.b^y.c^z=bc.ca.ab=a^2.b^2.c^2\)\(\Leftrightarrow\frac{a^2.b^2.c^2}{a^x.b^y.c^z}=1\Rightarrow\frac{a^2}{a^x}.\frac{b^2}{b^y}.\frac{c^2}{c^z}=1\)
Do a;b;c;x;y;z>0;a;b;c>1\(\Rightarrow\hept{\begin{cases}\frac{a^2}{a^x}=1\\\frac{b^2}{b^y}=1\\\frac{c^2}{c^z}=1\end{cases}}\Rightarrow\hept{\begin{cases}a^2=a^x\\b^2=b^y\\c^2=c^z\end{cases}}\Rightarrow x=y=z=2\)
\(\Rightarrow\hept{\begin{cases}x+y+z+2=2+2+2+2=4\\x.y.z=2.2.2=4\end{cases}}\Rightarrow x+y+z+2=xyz\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có :
\(\frac{ab}{a+b}=\frac{bc}{b+c}=\frac{ca}{c+a}=\frac{ab-bc}{\left(a+b\right)-\left(b+c\right)}=\frac{bc-ca}{\left(b+c\right)-\left(c+a\right)}=\frac{ab-ca}{\left(a+b\right)-\left(c+a\right)}\)
\(\Rightarrow a=b=c\)
\(\Rightarrow Q=\frac{ab^2+bc^2+ca^2}{a^3+b^3+c^3}=1\)
Ta có: a+b+c=0 => (a+b+c)2=0
<=> a2+b2+c2+2ab+2bc+2ca=0
=> \(ab+bc+ca=-\frac{1}{2}\left(a^2+b^2+c^2\right)\)
Mà: \(a^2;b^2;c^2\ge0\) => \(a^2+b^2+c^2\ge0\)=> \(-\frac{1}{2}\left(a^2+b^2+c^2\right)\le0\)
=> \(ab+bc+ca=-\frac{1}{2}\left(a^2+b^2+c^2\right)\le0\)